2021
DOI: 10.1051/e3sconf/202127408003
|View full text |Cite
|
Sign up to set email alerts
|

Testing heat supply networks for heat losses

Abstract: The scope of operations of the branch where the survey was carried out is: transmission and distribution of heat and heating medium to consumers through heat supply networks, maintaining the proper quality and amount of thermal power and heating medium supplied, ensuring contractual activities with heat consumers, as well as control of compliance with the consumption regimes stipulated by contracts, ensuring payments from consumers for supplied heat and heating medium, development and implementation of measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The behaviour of insulating materials for high-temperature supply systems, such as district heating networks, has received increasing interest [3]. Field tests found that the actual heat losses exceed the standard values by 1.21-1.35 times in heat networks [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviour of insulating materials for high-temperature supply systems, such as district heating networks, has received increasing interest [3]. Field tests found that the actual heat losses exceed the standard values by 1.21-1.35 times in heat networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of insulating materials for high-temperature supply systems, such as district heating networks, has received increasing interest [3]. Field tests found that the actual heat losses exceed the standard values by 1.21-1.35 times in heat networks [3]. These results emphasise the need to develop durable materials with a stable behaviour even at temperatures of several hundred Celsius degrees.…”
Section: Introductionmentioning
confidence: 99%